On‐site detection of bypass circuit opening failure in photovoltaic array under power generation operation. Issue 9 (5th June 2020) - Baba, Masaaki; Itami, Daichi; Yamada, Noboru
Abstract: To ensure the long‐term reliability of photovoltaic systems (PVSs), periodical inspections are necessary. Despite the risk of severe temperature rise, bypass circuit open‐circuit (BPC‐OC) failure has attracted low research interest compared with other types of failure. This paper presents the pulsed light irradiation (PLI) method for robust BPC‐OC failure detection that eliminates the need to switch off the power generation operation of the PVS. The proposed method detects the BPC‐OC failure of the solar cell string by measuring the modulated current induced by local PLI. Electrical circuit simulations as well as indoor and outdoor experiments are performed to verify the performance of the proposed method. Results of the outdoor experiment show that the PLI method performs well in a real PVS under power generation operation. Finally, the advantages and disadvantages of the proposed method are summarized. Abstract : A bypass circuit open‐circuit (BPC‐OC) failure increases the risk of severe temperature rise in the solar cells of photovoltaic modules. This paper presents the pulsed light irradiation (PLI) method for BPC‐OC failure detection without shutting down the power generation operation of the photovoltaic system (PVS). Electrical circuit simulations, as well as indoor and outdoor experiments, were carried out to verify that the PLI method can detect BPC‐OC failure of a PV module in a real PVS under fluctuating solar irradiation using low‐cost instruments.